An integrated land-use/transportation forecasting and planning model: A metropolitan planning support system - Ardeshir Anjomani (Journal of Transport and Land Use)
Over the last several decades, land-use/transport interaction models have evolved. Although these models have the potential to become primary demographic forecasting and planning vehicles in metropolitan transportation planning for most large US urban regions, some gaps and improvements must be addressed.